SIFAT FISIK TANAH MINERAL MASAM INCEPTISOL PADA LAHAN PERKEBUNAN KELAPA SAWIT YANG DITANAMI LCC Mucuna sp. DENGAN PEMBERIAN CACING TANAH Pontoscolex sp. - Rifqi Nugraha; Wawan Wawan; Wardati Wardati (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2019)
The research aims to study the effect of combination of LCC Mucuna sp. and earthworms Pontoscolex sp. and to obtain the best combination treatment on physical changes of the inceptisol at the plam plantation. The experiment has been conducted at the experimental farm of the Faculty of Agriculture University of Riau, Pekanbaru from Februari to Juni 2018. The experimental unit was arranged in a completely ramdomized design (RAL), consisting of 9 combinations of the ground the LCC Mucuna sp. with the feeding of the earthworms Pontoscolex sp. and repeated it 3 times. Parameter observed were the rate of infiltration, water level, bulk density, particle density, total pore spaces, permeability and soil organic matter. Data were analyzed statistically using analysis of variance and comparemean of variables observed by using Duncan New Multiple Range Test an significant level of 5 %. The result showed an increase in combinations of the ground the LCC Mucuna sp. with the feeding of the earthworms Pontoscolex sp. increase water levels, total pore spaces and organic material soils and tend to increase rate of infiltration, particle density and permeability and decrease bulk density at the oil palm wicket. The combinations treatment LCC Mucuna sp. 8 plants/plot with eartworms Pontoscolex sp. 45 tails/plot produced in a change in the best physical properties of the soil compared with other treatments.Keyword: LCC Mucuna sp., earthworms Pontoscolex sp